Narečna literatura kot značilnost "manjšinjske literature"? - Cergol, Jadranka (Jezik in slovstvo, 2016)
The purpose of the paper is to demonstrate that dialect literature is one of the main characteristics of minority literature. Previous studies have shown that Slovenian dialect literature arises primarily on the outskirts of the Slovenian ethnic settlement area, in neighbouring countries and even in those areas where the Slovenian language comes into contact with other languages. Analysing the cases of two minority communities - Slovenians in Italy and the Italian minority in Slovenia and Croatia - the author attempts to demonstrate that dialect literature is a very typical phenomenon in minority literature and displays a special relationship to language in general.
Keywords: Slovenci v Italiji; manjšinska književnost; narečna književnost; dialect literature; slovenska zamejska književnost; Italija; Italy; Slovenia; Slovenija; Hrvaška; Croatia